Untangling the R2* contrast in multiple sclerosis: A combined MRI-histology study at 7.0 Tesla - Bagnato, Francesca (PLoS One, 2018)
T2*-weighted multi-echo gradient-echo magnetic resonance imaging and its reciprocal R2* are used in brain imaging due to their sensitivity to iron content. In patients with multiple sclerosis who display pathological alterations in iron and myelin contents, the use of R2* may offer a unique way to untangle mechanisms of disease. Coronal slices from 8 brains of deceased multiple sclerosis patients were imaged using a whole-body 7.0 Tesla MRI scanner. The scanning protocol included three-dimensional (3D) T2*-w multi-echo gradient-echo and 2D T2-w turbo spin echo (TSE) sequences. Histopathological analyses of myelin and iron content were done using Luxol fast blue and proteolipid myelin staining and 3,3′-diaminobenzidine tetrahydrochloride enhanced Turnbull blue staining. Quantification of R2*, myelin and iron intensity were obtained. Variations in R2* were found to be affected differently by myelin and iron content in different regions of multiple sclerosis brains. The data shall inform clinical investigators in addressing the role of T2*/R2* variations as a biomarker of tissue integrity in brains of MS patients, in vivo.